Validating the functional design of embedded systems against stakeholder intentions - Daun, Marian; Weyer, Thorsten; Pohl, Klaus (2014 2nd International Conference on Model-Driven Engineering and Software Development (MODELSWARD), 2014)
In the embedded systems industry, function-centered engineering is commonly applied to address the increasing number and complexity of system functions. During function-centered engineering, the functional design that is created based on the defined requirements for the system is the main artifact that serves as a basis for subsequent development activities. If stakeholder intentions change and modifications become necessary, they are frequently incorporated directly into the functional design without updating the behavioral requirements accordingly. As a consequence, the correctness of the interplay of system functions as defined in the functional design cannot be assessed by checking it against the defined requirements (since they are outdated) but needs to be checked against the current stakeholder intentions. More precisely, the requirements engineer has to validate the functional design against the stakeholder intentions because he is the expert concerning the stakeholder intentions and can communicate with the stakeholders regarding them, if necessary. However, the requirements engineer is typically not familiar with the functional design and its notation on the one hand, and, on the other hand, the overall behavior of the system is spread across various diagrams in the functional design. Therefore, the requirements engineer needs a more abstract and consolidated view of the functional design in order to be able to validate its correctness with regard to the current stakeholder intentions. In this paper, we present an approach which is based on a specific kind of review model that is automatically generated from the functional design and supports the requirements engineer in her task. The approach that is presented in this paper is subject of ongoing research.